Tissue-Engineered Human Myobundle System as a Platform for Evaluation of Skeletal Muscle Injury Biomarkers. (6th May 2020) - Khodabukus, Alastair; Kaza, Amulya; Wang, Jason; Prabhu, Neel; Goldstein, Richard; Vaidya, Vishal S; Bursac, Nenad
Abstract: Traditional serum biomarkers used to assess skeletal muscle damage, such as activity of creatine kinase (CK), lack tissue specificity and sensitivity, hindering early detection of drug-induced myopathies. Recently, a novel four-factor skeletal muscle injury panel (MIP) of biomarkers consisting of skeletal troponin I (sTnI), CK mass (CKm), fatty-acid-binding protein 3 (Fabp3), and myosin light chain 3, has been shown to have increased tissue specificity and sensitivity in rodent models of skeletal muscle injury. Here, we evaluated if a previously established model of tissue-engineered functional human skeletal muscle (myobundle) can allow detection of the MIP biomarkers after injury or drug-induced myotoxicity in vitro. We found that concentrations of three MIP biomarkers (sTnI, CKm, and Fabp3) in myobundle culture media significantly increased in response to injury by a known snake venom (notexin). Cerivastatin, a known myotoxic statin, but not pravastatin, induced significant loss of myobundle contractile function, myotube atrophy, and increased release of both traditional and novel biomarkers. In contrast, dexamethasone induced significant loss of myobundle contractile function and myotube atrophy, but decreased the release of both traditional and novel biomarkers. Dexamethasone also increased levels of matrix metalloproteinase-2 and -3 in the culture media which correlated with increased remodeling of myobundle extracellular matrix. In conclusion, this proof-of-concept study demonstrates that tissue-engineered human myobundles can provide an in vitro platform to probe patient-specific drug-induced myotoxicity and performance assessment of novel injury biomarkers to guide preclinical and clinical drug development studies.